Novel Food-Based Enrichment Increases Captive Cownose Stingray (Rhinoptera bonasus) Engagement with Enrichment Item - Mia C. Y. Harris; Heidi Frazier; Sean Mayall; Alexandra D. Frey; Sarah A. Boyle (Journal of Zoological and Botanical Gardens)
Environmental enrichment can provide captive animals with stimuli that increase physical and mental activity. We investigated the extent to which a novel enrichment item, defined as enrichment that individuals have never experienced prior to the study, engages captive cownose stingrays (Rhinoptera bonasus). We hypothesized that stingray interactions with the enrichment item are associated with the novelty of the enrichment item (i.e., time since presentation of the enrichment item, number of weeks exposed to the enrichment), the presence of food, and the number of human visitors at the stingray exhibit. The novelty of the enrichment item and the presence of food were most strongly associated with stingray interactions with the enrichment item. Although stingrays engaged with the enrichment throughout a 5-week period, interactions decreased as the amount of time the enrichment item remained in the water increased during a 60 min period and interactions decreased as the weeks progressed. Furthermore, stingrays had increased interactions when food was present inside the enrichment item. The number of human visitors had a weaker association with stingray interactions with the enrichment item, but during the food-based trials, there were increased interactions with the enrichment when more visitors were present. Our findings suggest that variation in enrichment routines (to maintain novelty) and variation in an enrichment item’s use of food may help continue engagement with enrichment items.